2020
DOI: 10.48550/arxiv.2003.09767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Group actions on twisted sums of Banach spaces

Abstract: We study bounded actions of groups and semigroups on exact sequences of Banach spaces, characterizing different type of actions in terms of commutator estimates satisfied by the quasi-linear map associated to the exact sequence. As a special and important case, actions on interpolation scales are related to actions on the exact sequence induced by the scale through the Rochberg-Weiss theory [30]. Consequences are presented in the cases of certain non-unitarizable triangular representations of the group F ∞ on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The role of the ambient space was considered in [10]. There it was shown that given two quasilinear maps Φ, Ψ : X Y , the former with ambient space A and the second with ambient space B then one can consider that both maps have a certain common space C as ambient space.…”
Section: Quasilinear Maps and Twisted Sums In A Broader Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of the ambient space was considered in [10]. There it was shown that given two quasilinear maps Φ, Ψ : X Y , the former with ambient space A and the second with ambient space B then one can consider that both maps have a certain common space C as ambient space.…”
Section: Quasilinear Maps and Twisted Sums In A Broader Contextmentioning
confidence: 99%
“…The notions of domain and range of centralizer-like mappings Ω : X Y have been considered in [7][8][9][10].…”
Section: Definition 22 a Quasilinear Map ω : Xmentioning
confidence: 99%
See 1 more Smart Citation